Comparative study of short prediction MPC-KF with PI controller for DC-DC buck converter - Erliza, Serri; Abu Zaharin, Ahmad (IEEE, 2017)
In nature, the DC-DC converter deals with high switching phenomenon that contributes to the higher conduction losses. Its operation conventionally associated with PI/PID controller in order to meet the desired output. To increase the DC-DC converter performance, an advanced controller has been proposed. However, it is deals with complex algorithm that made the controller cost higher. In this paper, the short prediction horizon of MPC using search tree optimization that generates low switching phenomenon is proposed. The optimal problem is being solve using on-line to reduce the computational effort. The Kalman filter is then used for load estimation. This control approach for DC-DC converter has produced the promising output transient performance when compared with conventional PI controller while also minimizing the switching losses phenomenon.